Improvement of the California Bearing Ratio of Peat Soil Using Soybean Crude Urease Calcite Precipitation - Heriansyah Putra; Irgie Yudhistira (Salehan Institute of Higher Education, 2022)
Due to its high organic matter, moisture content, and low bearing capacity, peat soil needs to be stabilized for use as a subgrade. The soybean crude urease calcite precipitation (SCU-CP) method is a grouting technique using carbonate precipitation and soybean as a biocatalyst. This study aims to analyze the effect of the SCU-CP method and soil density on the California bearing ratio (CBR) value to obtain the best stabilization alternative for reducing the field’s compaction energy. The CBR test was conducted in both soaked and unsoaked conditions. The study was conducted with variations of 50%, 70%, and 90% density of Standard Proctor and used grouting treatment with a combination of optimum SCU-CP solution for the treated samples. The results showed a significant increase in CBR, with an average increase of more than two times compared to untreated samples. In terms of compaction effort, a density of 70% Proctor in unsoaked conditions with SCU-CP treatment is the best alternative. However, considering the soil saturation level and the swelling of the subgrade layer, 90% proctor density with SCU-CP treatment can be recommended as a stabilization method without dewatering. This research concluded that the SCU-CP method could improve the CBR value of peat soil. Doi: 10.28991/CEJ-2022-08-11-04 Full Text: PDF